Vocation and Mobility as Significant Modifiable Determinants For Quality Of Life Among Oral And Throat Cancer Patients - A Hospital Based Study From Southern India - jain, Smriti; Susila T; Duraisamy, Senthil Arasi; Krithiga Sivakumar; Sameeya Furmeen Salam; Punithakumary P; Seenivasan P (National Journal of Community Medicine, 2023)
Background: Quality of Life (QOL) is an important indicator of treatment outcome for cancer therapies. QOL researches help us to explore about the impairment caused by treatment and disease on one’s social life, day to day activities and psychological conditions. The objective is to assess the health related QOL in patients suffering from oral cavity and throat cancer and to find out factors associated with QOL. Methodology: Facility based cross sectional study design with consecutive sampling was used to achieve a sample size of 90 patients with oral cavity and throat cancer. Result: 71(78.88%) of study participants were independent and 19(21.11%) were partially dependent, none were completely dependent. Majority of the study population perceived a poor overall QOL as revelled by the findings that only 24.4% had best scoring in overall QOL domain. Weak Positive Correlation (R2=0.224) was seen between physical and socio- emotional component of QOL (p value <0.001). Education and cancer site were significantly associated with physical component while employment and Activity of Daily Living were associated with social component of QOL. Conclusion: There is a need to focus on ambulatory and vocational rehabilitation along with pain management for oral & throat CA patients as the study show an association of these factors with social component of QOL.